2019
DOI: 10.21273/hortsci13850-18
|View full text |Cite
|
Sign up to set email alerts
|

Net Houses Effects on Microclimate, Production, and Plant Protection of White-fleshed Pitaya

Abstract: Additional index words. cladode, flowering, fruit quality, bagging, pests and diseases, sunburn Abstract. To evaluate the comprehensive response of commercial cultivation of the whitefleshed pitaya (Hylocereus undatus 'VN White') under net house in Taiwan, experiments were conducted during the natural reproductive period (from June to Sept. 2016) with fruits grown within net houses (either 16 or 24 mesh insect-proof netting, without fruit bagging) or in an open field (the control, without netting, with fruit b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…'Da Hong', also known as 'Big Red', is an elite red-fleshed cultivar preferred by growers in Taiwan and Southeast Asia because of its favorable traits including self-compatibility, abundant yield, large fruit (more than 400 g per fruit), and high total soluble solid content (TSSC, above 20°Brix) (Jiang and Yang, 2015;Liu et al, 2015). However, unlike the redfleshed cultivar Fu Gui Hong or VN White, a white-fleshed pitaya (H. undatus) cultivar, Da Hong does not produce high fruit yield all of the year in Taiwan (Chien and Chang, 2019). It has been found that although 'Da Hong' produces the most abundant flowers and fruits during the hottest period (August to September), the fruits are small (less than 150 g) and the color of the cladode becomes yellow under field conditions (Y.C.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…'Da Hong', also known as 'Big Red', is an elite red-fleshed cultivar preferred by growers in Taiwan and Southeast Asia because of its favorable traits including self-compatibility, abundant yield, large fruit (more than 400 g per fruit), and high total soluble solid content (TSSC, above 20°Brix) (Jiang and Yang, 2015;Liu et al, 2015). However, unlike the redfleshed cultivar Fu Gui Hong or VN White, a white-fleshed pitaya (H. undatus) cultivar, Da Hong does not produce high fruit yield all of the year in Taiwan (Chien and Chang, 2019). It has been found that although 'Da Hong' produces the most abundant flowers and fruits during the hottest period (August to September), the fruits are small (less than 150 g) and the color of the cladode becomes yellow under field conditions (Y.C.…”
mentioning
confidence: 99%
“…Although pitaya has a crassulacean acid metabolism (CAM) characteristic, it is prone to yellowing of the cladode, i.e., slight sunburn with no incidence of necrosis on the sunny (sun-exposed) side of the adaxial cladode that has three flat wavy ribs with one sunny side and two shaded sides in redfleshed pitaya, during the hot season in Taiwan, followed by regreening during cooler seasons (Chien and Chang, 2019). Of the pitayas, the cladode of the white-flesh pitaya displays the highest total daily net uptake of CO 2 at day/night air temperatures of 30/20°C, but the total daily net uptake of CO 2 falls remarkably at 40/30°C (Nobel and De la Barrera, 2002), indicating that dry matter accumulation may be affected by temperature regimes.…”
mentioning
confidence: 99%
“…However, traditional strategies to protect the fruits by using insecticides may pose residual risks to the fruit, the environment and human health ( Devine and Furlong, 2007 ); in addition, application of insecticides may not completely eliminate the insects, possibly due to the development of insect resistance ( Sparks et al, 2020 ), as confirmed by the results of our study ( Figure 1C ). IPNs are suitable tools for insect control ( Formisano et al, 2020a ) and have been widely used on vegetables, melons and fruits ( Chien and Chang, 2019 ; Formisano et al, 2020b ). However, the effects of IPNs on Chinese bayberry fruits have not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…During the peak of summer (June-August) in Taiwan, the day and night temperatures are close to 35 • C and 25 • C, respectively [15]. Under this environment of high light intensity and elevated temperature, the sun-exposed shoots at the adaxial end often burn and exhibit yellowing, and the yellowed shoots naturally re-green in autumn (October) when the temperature decreases [15]. During HT, a 50% sunshade net placed above the canopy can lower the temperature and reduce the yellowing of shoots [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Under this environment of high light intensity and elevated temperature, the sun-exposed shoots at the adaxial end often burn and exhibit yellowing, and the yellowed shoots naturally re-green in autumn (October) when the temperature decreases [15]. During HT, a 50% sunshade net placed above the canopy can lower the temperature and reduce the yellowing of shoots [15][16][17][18]. However, compared with the findings in an open field, the yellowing of shoot in plants cultivated in a netting facility is not improved even though the light intensity is reduced, owing to the increase in temperature [15].…”
Section: Introductionmentioning
confidence: 99%